1987
DOI: 10.1111/j.1747-6593.1987.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Plumbosolvency Propensity to Guide the Control of Lead in Tapwaters

Abstract: SYNOPSISA LABORATORY-SCALE lead-pipe rig has been developed into an accelerated test for 'plumbosolvency propensity'. High alkalinity water supplies from Anglian Water show either relatively high or low propensity characteristics which appear to be related to the form of the crystal deposit. These have been examined by scanning electron microscopy. The paper describes the uses of the test to (1) supplement random survey data, (2) investigate mixed waters, and (3) optimize orthophosphate dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 1 publication
0
22
2
Order By: Relevance
“…Laboratory plumbosolvency testing was undertaken by the standard method developed by Colling et al (1987Colling et al ( , 1992 for the major works requiring ortho-phosphate dosing and for a representative selection of the minor works requiring ortho-phosphate dosing. Testing involves pumping test water through sections of new lead piping at 258C with a water-pipe contact time of 30 minutes and measuring the lead emissions over a four week period.…”
Section: Ortho-phosphate Dose Selectionmentioning
confidence: 99%
“…Laboratory plumbosolvency testing was undertaken by the standard method developed by Colling et al (1987Colling et al ( , 1992 for the major works requiring ortho-phosphate dosing and for a representative selection of the minor works requiring ortho-phosphate dosing. Testing involves pumping test water through sections of new lead piping at 258C with a water-pipe contact time of 30 minutes and measuring the lead emissions over a four week period.…”
Section: Ortho-phosphate Dose Selectionmentioning
confidence: 99%
“…Although a wide range of doses have been applied (<0.1 to >1 mg/L as P), doses in the range of 1 to 1.6 mg/L as P are recommended for limiting lead corrosion by‐product release (Edwards et al, 1999). For example, an 80% decrease in lead concentration has been observed with a dose of 1 mg/L as P (Colling et al, 1988). Other researchers reported that lead concentrations decreased to <15 μg/L with a dose of 1.5 mg/L as P in pipe‐loop testing with both new and old lead pipes (Cantor et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive laboratory-based plumbosolvency testing in the UK using the method of Colling et al (1987) indicates (Hayes 2007) that all types of drinking water in supply are likely to be sufficiently plumbosolvent so as to cause non-compliance with both the EU standards for lead (i.e. 10 and 25 mg l 21 ) wherever lead pipes are present Taken together, these two studies suggest that around 65% of houses that have a lead pipe, either as a connection pipe or as internal piping, can be expected to exceed the EU's lead standard of 10 mg l 21 , unless corrosion inhibitor is dosed (and correctly so), which in the EU is not common outside the UK.…”
Section: Emerging Evidence Of Problemsmentioning
confidence: 99%